2017
DOI: 10.1177/0886260517715601
|View full text |Cite
|
Sign up to set email alerts
|

Classes of Intimate Partner Violence From Late Adolescence to Young Adulthood

Abstract: Researchers do not agree on how intimate partner violence (IPV) emerges and changes from adolescence to young adulthood. This may be because change in these behaviors varies across individuals. The present study uses a longitudinal, person-centered approach to examine whether there are multiple classes or patterns of change in the perpetration of IPV during the transitional period from adolescence (age 18) to young adulthood (age 25) using data collected annually from a community sample of 484 participants. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
(105 reference statements)
3
20
0
1
Order By: Relevance
“…Previous studies hinted at the possibility of diversity in the expression of IPV over time across a sample/population (Capaldi et al, 2003;Foshee et al, 2009;Fritz & O'Leary, 2004;Fritz & Slep, 2009;Kim et al, 2008;Nocentini et al, 2010;O'Leary & Slep, 2003;Orpinas et al, 2013;Orpinas et al, 2012;Swartout et al, 2012). Saint-Eloi Cadely et al (2020) explored this diversity with a person-centered approach and identified multiple patterns of IPV across an 8-year period from ages 18 to 25. This approach classified individuals into different subgroups by minimizing differences within groups and maximizing differences between them (Swartout et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies hinted at the possibility of diversity in the expression of IPV over time across a sample/population (Capaldi et al, 2003;Foshee et al, 2009;Fritz & O'Leary, 2004;Fritz & Slep, 2009;Kim et al, 2008;Nocentini et al, 2010;O'Leary & Slep, 2003;Orpinas et al, 2013;Orpinas et al, 2012;Swartout et al, 2012). Saint-Eloi Cadely et al (2020) explored this diversity with a person-centered approach and identified multiple patterns of IPV across an 8-year period from ages 18 to 25. This approach classified individuals into different subgroups by minimizing differences within groups and maximizing differences between them (Swartout et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IPV classes reflected patterns in the usage of psychological and physical IPV over time. Details pertaining to the assessment of IPV utilized in the classification are available in Saint-Eloi Cadely et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Para ello, se aplicó un análisis de clases latentes (ACL), una técnica de interdependencia poco empleada en el ámbito de estudio de la violencia contra las mujeres (vid. Ansara y Hindin 2010; Parker et al 2016;Saint-Eloy et al 2017) y de la cual no se tiene constancia de que haya sido aplicada al estudio de los mitos sobre la violencia de género, lo que supone una novedad de esta investigación. Partiendo de la interdependencia de estos mitos y creencias (Bosch y Ferrer 2012; Policastro y Payne 2013), el ACL permite explorar los patrones de adhesión a través de la identificación de clases que más tarde serán utilizadas para examinar su vinculación con la ideología sexista y las experiencias de victimización en el ámbito de las relaciones de pareja.…”
Section: Presente Estudiounclassified